The Evolution of Urban Australian Meat-Eating Practices - Khara, Tani; Riedy, Christopher; Ruby, Matthew B. (Frontiers in Sustainable Food Systems, 2021)
This qualitative study used social practice theory to explore how meat-eating practices are changing in contemporary urban Australia, drawing on a sample of Sydney residents aged 23-45 years. The research used an iterative study design and an inductive analysis approach. Semi-structured face-to-face in-depth interviews were the main mode of data collection. These were supplemented by observations of meat-eating practices in public places such as restaurants, markets and local neighbourhoods. Research participants in this study explained that the role of meat in their diet has changed in response to shifting conventions, norms and social infrastructures. Many have reduced their consumption of red meat in favour of meats considered more ethical, environmentally friendly or healthier. Key factors driving the change include exposure to alternative eating practices brought about through changes in political policy, the advent of globalisation and messages relating to meat and animal welfare in the media. The shift away from Australian masculine stereotypes as well as rising consciousness of environmental and health-related issued have also contributed to the dietary changes. There was some evidence that participants had also increased their consumption of plant-based foods. However, meat continues to maintain a significant presence within the Australian diet. While many expressed interest in cutting back further on meat consumption and adopting more plant-based foods, they identified several challenges – e.g., limited access to plant-based ingredients and recipes, negative meanings associated with vegetarian and vegan diets, and a lack of competence in relation to preparing and consuming healthy and appetizing plant-based meals.